Health Impact Database Development for Sweeteners and Sweetness Enhancers: The SWEET Project. - Scott, Corey E.; Stamataki, Nikoleta; Harrold, Joanne A.; Raben, Anne; Halford, Jason C. G. (Nutrition Bulletin, 2025)
Sweeteners and sweetness enhancers (S&SEs) are ingredients used in foods and beverages to reduce sugar while providing the sweetness of sugar with little to no calories. Although S&SEs have global regulatory approval and acceptance, questions remain regarding their overall safety and efficacy. Information on the effects of S&SEs in regard to health and efficacy can be found in randomised controlled trials (RCTs) that exist in peer‐reviewed literature. With the large number of RCT publications on various S&SEs, a need exists to organise and collect each of the published studies in a useful database. Currently, a database containing human clinical information on S&SEs does not exist and so The SWEET project has created a publicly available and comprehensive Health Impact Database that includes available human clinical information on sweeteners. This paper describes the process and development of a database that collects comprehensive information on published human clinical studies evaluating S&SEs between the years January 2000 and September 2024. Ovid Medline was used to search for RCT publications from the year 2000 to 2024. The search produced 1538 publications, of which 257 complied with the predetermined eligibility criteria. There was a large variability in the number of studies that fit the inclusion criteria. For example, some S&SEs had numerous studies (i.e., sucralose, n = 63 eligible publications) and some S&SEs had no publications that fit the criteria (aspartame‐acesulfame K salt and neohesperidine DC). The Health Impact Database is located at https://sweetproject.eu/HIdatabase and is contained in Microsoft Excel spreadsheets which are organised by health impact criteria. This database will be a useful tool for researchers as it provides comprehensive information on human clinical studies on S&SEs that can be leveraged as a general resource and for systematic reviews and meta‐analyses.